Statistical Scaling Laws for Competing Biological Species - Silva, Vinicius Barros da [UNESP] (Complex Systems Publications Inc, 2018)
Universality classes are defined for an idealized nonlinear system that governs the competition between biological species. The decay to asymptotic steady state is examined for supercritical Hopf bifurcation by considering a phenomenological approach supported by numerical simulations and confirmed by an analytical description. The formalism is general and it is expected to be universal for systems exhibiting Hopf bifurcations.
Keywords: scaling properties; critical exponents; prey-predator; Hopf bifurcation